E-049 Percutaneous embolization of clival dural AVF via foramen ovale. (4th July 2012) - Urdaneta, A; Chen, J; Chao, K; Feng, L
Abstract : Purpose: To evaluate the feasibility of percutaneous embolization of clival dural AVF with difficult venous access. Materials and Methods: A 69-year-old woman with EF of 15%–20% presented with a 9-month history of progressive right proptosis, chemosis, ophthalmoplegia and visual loss. Angiogram showed a small left clival dural AVF supplied by dural branches of bilateral meningohypophyseal trunks. The recipient vein was in the left dorsal clivus, superior and medial to the Meckel's cave. It drained underneath the posterior clinoid to its counterpart vein on the right side, connecting to a cortical vein and the right superior ophthalmic vein. The right cavernous sinus, right facial vein and bilateral inferior petrosal sinuses were occluded. There was no connection of the fistula to the left cavernous sinus. Transarterial embolization of bilateral meningohypophyseal trunks with Onyx resulted in only partial alleviation of her symptoms. Transvenous embolization was attempted but access to the left clival vein could not be established. Percutaneous embolization was thus planned using CT angiography. A 20 Gauge spinal needle was advanced into the left clival vein via the left foramen ovale under fluoroscopy guidance. The fistula was embolized with Onyx. Results: Angiographic cure of the dural AVF was immediately achieved. The patient's symptoms improved next day and completely resolved within 2 months. Follow-up angiogram showed durable occlusion of the fistula at 3 months. Conclusion: Dural AVF in the posterior cavernous sinus and dorsal clivus may be embolized percutaneously via foreman ovale. Competing interests: None.